Effectiveness of Giving Binahong Leaf Extract Capsules (Anredera Cordifolia) in Reducing Muscle Pain (DOMS) after Eccentric Exercisek - Daffa, Dary Raihan; Irawan, Roy Januardi (Universitas Padjadjaran, 2024)
Delayed Onset Muscles Soreness (DOMS) can cause muscle pain and functional limitations such as stiffness and decreased strength which if not properly addressed can adversely affect a person's performance in carrying out daily activities. The purpose of this study was to accelerate the decrease in DOMS muscle pain by knowing the effect of giving binahong leaf extract capsules in relieving DOMS symptoms after eccentric exercise This research uses experimental research with a Two Group Pretest Posttest Control Group Design design. Experimental research is a quantitative research method used to determine the effect of independent variables (treatment) on dependent variables (outcomes) under controlled conditions. The research subjects were divided into 2 groups, 10 experimental groups and 10 control groups. Binahong leaf extract capsules were given after the subject experienced DOMS after 24 hours of eccentric exercise at a dose of 1600 mg with 1 capsule containing 800 mg and then the subject consumed 2 capsules per day. Measurements were taken 24 hours after eccentric exercise when the subject experienced DOMS (pretest) and then given binahong leaf extract capsules, 48 hours after giving binahong leaf extract capsules, measurements were taken again (posttest). From the results of the study, it is known that the administration of binahong leaf extract capsules in the experimental group can reduce DOMS muscle pain at 48 hours after eccentric exercise by 4.92 ± 0.496 while in the treatment group it is 6.58 ± 0.664 with the difference between the post test of the experimental group and the control group by 1,28 (±0,282) and the percentage decrease is 35% with value p = 0,001 (p = <0,05)Keywords: DOMS, binahong leaf extract capsule, eccentric exercise.